Potential of Antithrombin III as a Biomarker of Antidepressive Effect in Major Depressive Disorder - Song, Ruize; Shi, Yachen; Li, Xianrui; Zhu, Jianli; Zhang, Hongxing; Li, Kun; Wang, Bi; Zhang, Haisan; Yang, Yongfeng; Gao, Lijuan; Zhao, Yang; Zhang, Zhijun (Frontiers in Psychiatry, 2021)
Background: The evaluation of treatment response to antidepressant therapy commonly depends on neuropsychologic assessments, as there are currently no suitable biomarkers. Previous research has identified a panel of increased proteins in patients with major depressive disorder (MDD), including antithrombin III (ATIII), as potential biomarkers of depression. Methods: A total of 90 MDD patients were recruited. Of these, 74 patients received occipital repetitive transcranial magnetic stimulation (rTMS) as individualized, standard, or sham treatment for five days, and underwent the complete procedure, including clinical assessments, blood collection, and protein measurement. Results: After treatment, ATIII was significantly decreased in both the individualized and standard groups (both p<0.001) relative to the sham group. In the individualized group, reduction in ATIII was associated with improvements in several neuropsychological assessments. Furthermore, ATIII at baseline in the standard group and after individualized rTMS showed good performance for evaluating or predicting the response to five-day treatment (AUC=0.771, 95%CI, 0.571-0.971; AUC=0.875, 95%CI, 0.714-1.000, respectively) and remission at follow-up (AUC=0.736, 95%CI, 0.529-0.943; AUC=0.828, 95%CI, 0.656-1.000, respectively). Lastly, both baseline ATIII and change in ATIII showed good predictive value for the 24-item Hamilton Depression Rating Scale at follow-up (p=0.024 and 0.023, respectively). Conclusion: Our study revealed a reduction in ATIII after occipital rTMS in MDD patients and a relationship between change in ATIII and therapeutic response. Taken together, these findings provide evidence for the potential of ATIII as a biomarker for the evaluation and prediction of antidepressive effects.